Structural and Immunological Activity Characterization of a Polysaccharide Isolated from Meretrix meretrix Linnaeus - Li Li; Heng Li; Jianying Qian; Yongfeng He; Jialin Zheng; Zhenming Lu; Zhenghong Xu; Jinsong Shi (Marine Drugs, 2015)
Polysaccharides from marine clams perform various biological activities, whereas information on structure is scarce. Here, a water-soluble polysaccharide MMPX-B2 was isolated from Meretrix meretrix Linnaeus. The proposed structure was deduced through characterization and its immunological activity was investigated. MMPX-B2 consisted of d-glucose and d-galctose residues at a molar ratio of 3.51:1.00. The average molecular weight of MMPX-B2 was 510 kDa. This polysaccharide possessed a main chain of (1→4)-linked-α-d-glucopyranosyl residues, partially substituted at the C-6 position by a few terminal β-d-galactose residues or branched chains consisting of (1→3)-linked β-d-galactose residues. Preliminary immunological tests in vitro showed that MMPX-B2 could stimulate the murine macrophages to release various cytokines, and the structure-activity relationship was then established. The present study demonstrated the potential immunological activity of MMPX-B2, and provided references for studying the active ingredients in M. meretrix.